EFFICACY OF EKAVINSHATIKA GUGGULU IN THE MANAGEMENT OF VICHARCHIKA - Pramod S. Mandalkar; Pradeep R. Bhabad; Nitin A. Gavhane; Rajesh T. Wankhade (International Journal of Applied Ayurved Research, 2015)
The study of Indian medical classics reveals that all skin diseases were included under the broad heading of Kushtha and which is classified in two divisions i.e. Mahakushtha and Kshudrakushtha. Vicharchika is enlisted under Kshudrakushtha. All type of Kushtha is Tridoshaja, so Vichachika is also having Tridoshaja origin with Kapha dominancy. Its similar clinical presentation in modern dermatology can be traced as Eczema. The modern science has greatly advanced, particularly in dermatology but there is no specific medicaments for sure cure of eczema but symptomatic treatments like steroids are used, but they produce serious side effects like nephrotoxicity, osteoporosis, skin cancer etc. Eczema also has tendency of recurrence which pose problems to the physician. Therefore, the whole world is looking towards Ayurveda for this problem to provide safe and effective remedy for Vicharchika. Considering all the above facts and figures in mind, the present study has been planned to assess the efficacy of Ekavinshatika Guggulu in the management of Vicharchika. For this purpose, 20 patients were selected from O.P.D. and I.P.D. of S.M.B.T. Ayurved College & Hospital, Dhamangoan and divided in two groups. In Group A: Ekavishantika Guggulu was given as internal medicine and Ekavinshatika Taila for external application, while in Group B: Kaishora Guggulu was given as internal medicine and Ekavinshatika Taila for external application. From obtained results it can be concluded that the efficacy of both groups are equal. Vicharchika (eczema) has tendency to recurrence. So, it was advisable to continue treatment for long time.